Ethnomathematics In Peresean Tradition - Rahmaniyah Rahmaniyah; Nafira Amelia; Desta Ahmad Saputra; Eka Kurniawan; Muhammad turmuzi (Sigma&Mu: Journal of Mathematics Education, Mathematics, Statistics and Data Science, 2026)
This study aims to identify and describe the manifestations of formal mathematical concepts contained in the Peresean tradition of the Sasak Tribe in Ende Traditional Village, Central Lombok. Peresean is a traditional martial art using a rattan stick (braid) and a leather shield (ende). This research includes qualitative research with an ethnographic approach. The data source was obtained through in-depth interviews with traditional leaders and participatory observations in the field. The results of the study show that there are mathematical concepts that are applied intuitively, including: (1) social arithmetic in the governance and distribution of spectator money in a fair manner both in formal competitions and the collective allocation of communal customary villages; (2) proportional linear function in the calculation of the logistical needs of the reserve forger; (3) traditional anthropometric proportions based on non-standard units (depa and jengkal) in determining the size of the braiding tool and the ergonomic ende for the fighter; and (4) the pattern of constant numbers over the duration of each round. This research is expected to contribute to the development of mathematics learning materials based on local culture (ethnomathematics).